Effect of Specimen Size and Curing Condition on the Compressive Strength of Alkali-Activated Concrete. Issue 1 (2017) - Thomas, Robert James; Peethamparan, Sulapha
Alkali-activated concrete is a rapidly emerging sustainable alternative to portland cement concrete. The compressive strength behavior of alkali-activated concrete has been reported by various studies to a limited extent, but these discussions have been based on minimal evidence. Furthermore, although it is known that specimen size has a distinct effect on the apparent compressive strength of concrete, this effect has yet to be modeled for alkali-activated concrete. This paper presents the results of a comprehensive study of the effects of curing condition (i.e., moist-cured at ambient temperature for 28 days or heat-cured at 50çC for 48 h) and specimen size on the compressive strength of sodium silicate–activated fly ash and slag cement concrete. The heat-cured strength of alkali-activated slag cement concrete was linearly related to the moist-cured strength; the former was about 5% greater than the latter. Heat curing also improved the strength of alkali-activated fly ash concrete, although the effect was greatly magnified for lower-strength mixtures and was much less significant at higher strengths. Existing size effect laws employed for portland cement concrete proved reasonably accurate in describing the effect of specimen size on the apparent strength of alkali-activated slag cement concrete. However, these existing models greatly underestimated the size effect in alkali-activated fly ash concrete; the authors suggest that this finding was the result of significant microcracking in the alkali-activated fly ash concrete.